PEMBIASAAN IBADAH HARIAN SEBAGAI STRATEGI PEMBENTUKAN GROWTH MINDSET SISWA KELAS RENDAH DI MADRASAH IBTIDAIYAH BAHRUL ULUM - Fairuz, Shofiyana Nadia; Raden Muhamad Hilmi Maulana; Lusiani Lestiana Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of daily religious habituation to the development of a growth mindset among lower-grade students in Islamic elementary schools (Madrasah Ibtidaiyah). The research employed a qualitative approach with a case study design at MI Bahrul Ulum, Bengle Karawang. The participants consisted of the principal, three Islamic Education teachers/classroom teachers, and twelve students from grades one to three. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings indicate that structured and consistent daily religious habituation creates repeated behaviors within a stable context, leading to the formation of religious habits and self-regulation. Indicators of growth mindset were reflected in students’ willingness to retry after making mistakes, persistence in facing learning difficulties, repeated practice to achieve mastery, and a transformation of motivation from extrinsic to intrinsic orientation. The integration of empirical findings with habit formation and growth mindset theories resulted in a conceptual model demonstrating that daily religious habituation functions as a contextual pedagogical strategy that gradually fosters long-term learning dispositions. This study expands the discourse on religious habituation beyond moral character formation toward a psychopedagogical perspective in Islamic elementary education.